Rancang Bangun Sistem Informasi Pendataan Anggota Sekolah Minggu Gereja Toraja Klasis Walenrang Timur Berbasis Web - Novela Mangiding, Novela; Solmin Paembonan; Dasril (Computer Science and Information Technology, 2024)
This research aims to design and build a web-based information system for data collection on members of the East Walenrang Toraja Church Sunday School. The research method used is the waterfall method. Data collection techniques used literature, interviews and observation. The design of a web-based information system for data collection on members of the East Walenrang Toraja Church Sunday School class was designed using the UML modeling language. The system was created using the PHP programming language, the Laravel Framework as data processing, HTML as the website display design and MySQL database as the data storage medium. The design of a web-based information system for data collection on members of the East Walenrang Toraja Church Sunday School was tested using Black Box testing to obtain an information system that worked well. Meanwhile, the results of usability testing are that this system is suitable for use.